2009
DOI: 10.1080/15548730802695105
|View full text |Cite
|
Sign up to set email alerts
|

Moving Beyond the Administrative: Supervisors' Perspectives on Clinical Supervision in Child Welfare

Abstract: This study contributes to the emerging knowledge base of child welfare supervision. An exploratory study examined the beliefs, practices, and experiences of 51 child welfare supervisors in Ontario, Canada. Eight focus groups were held with supervisors from a range of settings cross the province. The study identified a number of interwoven factors at the organizational, supervisory, and practice level that affect the nature of supervision offered. Implications are drawn for child welfare practice, models of sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…Other research related to child welfare supervision has focused on clinical supervision (Dill & Bogo, 2009;Lietz & Rounds, 2009) and the stress and job satisfaction of the supervisor (Collins-Camargo et al, 2009;Lee & Ashworth, 1993;Regehr, Chau, Leslie & Howe, 2004;Silver, Poulin & Manning, 1997) Only a handful of studies have addressed supervisory practice in child welfare (Clark et al, 2008;Dill & Bogo, 2009;Lietz & Rounds, 2009;Rushton & Nathan, 1996). Dill and Bogo (2009) found that the organizational context of child welfare has a large impact on the quality of clinical supervision. Handling the day-to-day personnel issues, managerial tasks, court work, and emergencies often preclude the ability of the supervisor to consistently provide individual supervision.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Other research related to child welfare supervision has focused on clinical supervision (Dill & Bogo, 2009;Lietz & Rounds, 2009) and the stress and job satisfaction of the supervisor (Collins-Camargo et al, 2009;Lee & Ashworth, 1993;Regehr, Chau, Leslie & Howe, 2004;Silver, Poulin & Manning, 1997) Only a handful of studies have addressed supervisory practice in child welfare (Clark et al, 2008;Dill & Bogo, 2009;Lietz & Rounds, 2009;Rushton & Nathan, 1996). Dill and Bogo (2009) found that the organizational context of child welfare has a large impact on the quality of clinical supervision. Handling the day-to-day personnel issues, managerial tasks, court work, and emergencies often preclude the ability of the supervisor to consistently provide individual supervision.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Dill and Bogo (2009) dedicated to the strengthening of the supervisor as a professional through educative supervision, they truly do not provide the best administrative supervision, as they become preoccupied with the idea of not being able to provide educative supervision to their own staff (Bogo & McKnight, 2005). Thus, good administrative supervision may come from good educative supervision; however good educative supervision rarely will come from administrative supervision.…”
Section: Different End Goalsmentioning
confidence: 99%
“…Attention should be given to increasing the awareness of supervisors regarding their use of professionalism, confrontation, and feedback" (p. 83). However, most literature focuses on the supervisor developing educational functions to become a better clinician, whereas there is little focus on becoming a better administrator (Bogo & McKnight, 2005;Dill & Bogo, 2009;Greenspan et al, 1994;Itshaky, 2001). …”
Section: Ableismmentioning
confidence: 99%
See 2 more Smart Citations